A novel subsurface adjustable dam for preventing active seawater intrusion in coastal aquifers - Chang, Qinpeng; Gao, Chenchen; Zheng, Xilai; Lin, Yucheng; Song, Xiaoran (Frontiers in Marine Science, 2024)
Subsurface physical barriers are widely used to prevent seawater intrusion in the world. After the construction of physical barriers, the residual saltwater is trapped upstream the barriers. Traditional physical barriers, including cutoff walls and subsurface dams, are fixed in structure and fail in prohibiting active seawater intrusion. In this work, a novel subsurface adjustable dam, composed of dam bodies and sluice gates, was designed to prevent active seawater intrusion and store groundwater flexibly according to seasonal variations in precipitation. We set three-dimensional field-scale numerical simulations to compare the control effects of adjustable dams, cutoff walls, and subsurface dams. The results revealed that the traditional subsurface physical barriers could mitigate the velocity of active seawater intrusion but were inadequate in completely preventing the intrusion process. Furthermore, although the traditional physical barriers temporarily alleviate the residual saltwater during the wet periods, the saltwater wedge would subsequently invade during next dry periods. Thus, the salt mass in the aquifer of traditional physical barriers scenarios exhibited a gradual annual increase. In contrast, the novel subsurface adjustable dam demonstrated the ability to prevent active seawater intrusion and remove the residual saltwater. During the dry periods, characterized by low precipitation recharge, the sluice gates were closed to obstruct the path of active seawater intrusion. Conversely, during the wet periods with abundant precipitation, the sluice gates were opened, facilitating the gradual removal of the residual saltwater. The flexible adjustment mechanism of subsurface adjustable dams resulted in a annual decrease in both the seawater intrusion length and the salt mass in the entire aquifer. These findings underscore the efficacy of the subsurface adjustable dam as a measure for preventing active seawater intrusion and simultaneously eliminating the residual saltwater.